Kant's Letter to Fichte, the Pure Intellect and his 'All-Crushing' Metaphysics: Comments on De Boer's Kant's Reform of Metaphysics. Issue 1 (March 2022) - Chance, Brian A.
Abstract: I raise three questions relevant to De Boer's overall project in Kant's Reform of Metaphysics . The first is whether Kant's 1799 open letter to Fichte supports or threatens her contention that Kant had an abiding interest in developing a reformed metaphysics from 1781 onwards. The second is whether De Boer's conception of the pure intellect and its place in Kant's projected system of metaphysics captures the role of pure sensibility in the Analytic of Principles, rational physics and rational psychology. The third is whether one might accept the outline of this system as De Boer develops it while still holding that it is more accurate to characterize it as revolution rather than reform.